Characteristics of motor abilities of young athletes of selected sports during sport training - Karpowicz, K.; Strzelczyk, R. (Studies in Physical Culture and Tourism, 2010)
The goal of the present study was to determine the structure of motor preparation of young athletes of selected sports in the context of their sport-specific training. The research material comprised results of investigations carried out among members of the Wielkopolska Province junior sport teams (canoeing, cycling, basketball, athletics, handball, volleyball, triathlon, rugby, rowing). The study encompassed 300 boys aged 15-16. The International Physical Fitness Tests and trials determining selected components of general physical preparation were used as the basic research tools. The study revealed that the structure of motor ability and its level often indicate premature effects of sport specialization, at the expense of comprehensive, well-balanced motor preparation.